Burkholderia cepacia Complex: Emerging Multihost Pathogens Equipped with a Wide Range of Virulence Factors and Determinants - Sílvia A. Sousa; Christian G. Ramos; Jorge H. Leitão (International Journal of Microbiology)
The Burkholderia cepacia complex (Bcc) comprises at least 17 closely-related species of the β-proteobacteria subdivision, widely distributed in natural and man-made inhabitats. Bcc bacteria are endowed with an extraordinary metabolic diversity and emerged in the 1980s as life-threatening and difficult-to-treat pathogens among patients suffering from cystic fibrosis. More recently, these bacteria became recognized as a threat to hospitalized patients suffering from other diseases, in particular oncological patients. In the present paper, we review these and other traits of Bcc bacteria, as well as some of the strategies used to identify and validate the virulence factors and determinants used by these bacteria. The identification and characterization of these virulence factors is expected to lead to the design of novel therapeutic strategies to fight the infections caused by these emergent multidrug resistant human pathogens.